Digital Doubt and Gendered Moral Policing: Social Media’s Role in Malay Atheist Identity Formation and Its Theological Implications - Razali, Kauthar; Senin, Nurhanisah; Mohammad Nasir, Nur Syahirah; Ghani, Muhammad Hafizuddin; Wangsanata, Susana Aditiya (Afkar: Jurnal Akidah dan Pemikiran Islam, 2025)
The perception of atheism as a Western concept faces new challenges as it emerges more visibly in Malaysia’s Malay Muslim-majority society, creating notable socio-cultural impacts. This research examines how online platforms catalyse deconversion, shape atheist worldviews, and reconfigure theological discourse. Using a qualitative case-study design, the researcher conducted semi-structured interviews with six self-identified Malay atheist millennials recruited through purposive snowball sampling, complemented by document analysis and digital ethnography of social media discourse; pseudonyms, encrypted storage and informed consent were used to safeguard anonymity Participants frequently linked their religious disengagement to family dynamics, social pressures, negative experiences with religious institutions, gendered enforcement and digitally mediated exposure to sceptical communities and content. Participants articulated their views in ways that demonstrate rational scepticism and support intellectual freedom. In contrast, participants perceive state and religious institutions as focusing on containment rather than engagement, thereby failing to address root causes. Overall, the research offers a novelty in linking Malay-Muslim socio-legal constraints with digital-mediated atheist identity formation and in specifying the ʿaqidah-level implications of “digital doubt” for how certainty, doubt and religious knowledge are justified in contemporary Malaysia.